Asian Journal of Law and Economics : The Official Publication of the Asian Law and Economics Association (De Gruyter, 2010)
EM‰The Asian Journal of Law and Economics/EM‰ (EM‰AJLE/EM‰) publishes high quality research in law and economics, both theoretical and empirical. It is the only journal that pays special attention to the economic aspect of laws in Asian countries. Although the editors are particularly interested in legal issues that originally occurred in Asia, they welcome submissions on any subject from any region without prejudice.